Seismic hazards along Ecuador, Perú and northern Chile (South America) - Prezzi, Claudia Beatriz (2015)
The western coast of South America is one of the most seismogenic zones of the world, due to the subduction of the oceanic Nazca Plate below South America. The spatial distribution of large-magnitude earthquakes or of their rupture areas indicates the existence of other large zones which could produce a large-magnitude earthquake in the future. The aim of this work was to study the historic seismicity along the coast of Ecuador, Perú and northern Chile through the analysis of the vertical stress anomalies and the application of the statistical method of Gumbel, with the major goal of estimating the probability of the occurrence of a large-magnitude earthquake during the actual decade. Earthquakes with Richter magnitude M ≥ 7 registered for the time intervals: 1541–1878 and 1895–2014 are considered. Our statistical analysis suggests the possible occurrence of a major earthquake in the study zone with a Richter magnitude ≥8.4/9.0. Taking into account the vertical stress anomalies detected in this study, it is considered that “the Arica seismic gap” identified in northern Chile could be the locus of the occurrence of such a major earthquake.